Early Experience With Pulmonary Root Translocation in Transposition of the Great Arteries With Left Ventricular Outflow Tract Obstruction. Issue 2 (March 2021) - Dharmapuram, Anil Kumar; Ramadoss, Nagarajan; Goutami, Vejendla; Verma, Sudeep; Pande, Shantanu
Background: The optimal surgical management of patients with transposition of the great arteries (TGA), ventricular septal defect (VSD), and left ventricular outflow tract obstruction (LVOTO) is debatable. This is our initial experience with pulmonary root translocation (PRT), a technique that aims to preserve the pulmonary valve function. Methods: From July 2012 to October 2019, 16 patients underwent anatomical repair for TGA, VSD, and LVOTO. The median age was 12 months (range: 7 months to 13 years), and the median weight was 7.75 kg (range: 5.6-29.5 kg). Thirteen patients had a diagnosis of d-TGA and three had congenitally corrected transposition of the great arteries (cc-TGA). The surgical technique involved PRT from the left ventricle (LV) to the right ventricle and routing the LV to the aorta. The left ventricular outflow tract orifice resulting from the pulmonary root extraction was closed with a pericardial patch. In patients with cc-TGA, an atrial switch operation was added. A bidirectional Glenn was necessary in four patients with a long LV to aorta tunnel. One patient required a transannular patch to reconstruct the right ventricular outflow tract (RVOT). Results: The median follow-up was 27 months. There was one hospital death due to residual mitral regurgitation. One patient died at home four months after hospital discharge. The remaining patients are doing well with adequate RVOT function and no valve regurgitation. Conclusions: Complete correction of TGA, VSD, and LVOTO using PRT was achieved with acceptable risk in patients with pliable and nondysplastic pulmonary valve. The translocated pulmonary root performed well in this short follow-up.